Tuberculous Arthritis of Knee Presenting as Baker’s Cyst: A Case Report (Delta Medical College Journal, 2020)
Background: Baker's cyst is usually degenerative in origin, infective etiology is rare and tubercular origin is exceptional. Tuberculosis (TB) of the musculoskeletal system is an uncommon infection caused by tuberculous bacilli and constitutes 1% - 5% of all forms of TB. About 30% of skeletal TB involves the joints, the knee being the 3rd most commonly affected after the spine and the hip. Knee tuberculosis commonly presents as synovitis or arthritis. We are presenting a case of a young female with clinico-radiological features suggestive of Baker's cyst. Complete excision of Baker's cyst and histopathology was done. Histopathological examination revealed multiple epitheloid granulomas pointing toward a tubercular etiology. Standard ATT protocol with rehabilitation was followed. The patient was asymptomatic at 1st year with complete resolution of symptoms and full range of motion. This case highlights the need to maintain high index of suspicion in cases hailing from endemic region with unusual intra-operative findings; also, the importance of routine histopathological examination.Delta Med Col J. Jul 2020;8(2): 101-104